Immobilization of 1,5,7-triazabicyclo [4.4.0] dec-5-ene over mesoporous materials: an efficient catalyst for michael-addition reactions under solvent-free condition - Kalita, Pranjal; Kumar, Rajiv (Applied Catalysis A-General, 2011)
Immobilization of 1,5,7-triazabicyclo [4.4.0] dec-5-ene (TBD, a bicylic guanidine base) over mesoporous material like SBA-15 has been found to be an excellent catalyst for Michael-addition of beta-nitro styrene with malonate. The reactions were performed under solvent-free condition at 373 K for 9 h. A wide variety of Michael donors and acceptors were investigated. Among them, high yield of Michael product was obtained for the reaction between p-Cl-nitrostyrene with dimethyl malonate. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 1; 5; 7-triazabicyclo[4.4.0] dec-5-ene; beta-nitro styrene and malonate; mesoporous materials; Michael-addition

Synthesis, characterization and electrochemical investigations of mixed-ligand copper(II)-organic supramolecular frameworks - Singh, Sandeep K.; Srivastava, Ashish Kumar; Srivastava, Krishna; Banerjee, Rahul; Prasad, Jagdish (Journal of Molecular Structure, 2017)
Two mixed-ligand copper(II)-organic coordination compounds with 5,5'-dimethyl-2,2'-bipyridine (5,5'-Me(2)bpy) as a primary ligand while aliphatic malonate (Hmal) and aromatic 2-hydroxynicotinate (2-OHNA) as secondary ligands, were synthesized. These complexes are formulated as: [Cu(Hmal)(5,5'-Me(2)bPY)(H2O)](ClO4) 1 and [Cu-2(2-OHNA)(2)(5,5'-Me(2)bpy)(2)(NO3)KNO3) 2. These two complexes were structurally characterized by single crystal X-ray diffraction analysis. Characterization was further supported by powder X-ray diffraction analysis, elemental analyses, FT-IR, FAB-MASS and TGA, DSC studies. Cyclic voltammetric and UV-visible spectral studies of these two complexes have also been done. The electrochemical studies of complex 1 in DMSO and DMF have shown that this complex undergoes quasi reversible diffusion-controlled one-electron transfer reaction without any chemical complication while complex 2 in DMSO undergoes quasi-reversible diffusion-controlled one electron transfer reaction, following EC mechanism. The electrochemical behaviour of complex 2 in DMF is complicated probably due to presence of more than one species in solution phase. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: 2 '-bipyridine; 3; 5; 5 '-dimethyl-2; 5-Tricarboxylic acid; Benzene-1; classification; Co-ordination-Compounds; Crystal-structures; cyclic voltammetry; magnetic properties; metal organic framework; Mixed-ligand complex; pi-pi stacking interaction; Polymers; Secondery Building Unit; Structural data; Supramolecular framework; Ternare Komplexe; X-ray diffraction